The distributional effect of a massive exodus in Latin America and the role of downgrading and regularization - Carlo Lombardo; Julian Martinez-Correa; Leonardo Pe\~naloza-Pacheco; Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2021)
The massive displacement of Venezuelan citizens to Colombia is the second most important episode of forced migration in the world. We study the impact of this demographic shock on the Colombian income distribution exploiting the geographical heterogeneity in the intensity of migration. We use RIF regressions in an instrumental variables approach to account for the non-random pattern of location of immigrants. We find that despite the fact that Venezuelan immigrants are relatively skilled compared to native Colombian workers, the exodus had a larger negative effect on the lower tail of the wage distribution, implying increases in income inequality and poverty. We link this result to a sizeable downgrading of (mostly unregistered) Venezuelan recent migrants who work in more routine tasks and earn lower wages than natives with similar characteristics. We also explore a large regularization program for immigrants and find that it was associated to a reduction in the extent of downgrading, and hence, to a mitigation of the unequalizing impact of the exodus.
Keywords: F14; F22; F16; F23; J61; L60; 330; Migration; Income; Inequality; Labor Markets; Downgrading; Colombia; Venezuela